2003
DOI: 10.1016/s1534-5807(03)00094-7
|View full text |Cite
|
Sign up to set email alerts
|

JNK1 Is Required for Maintenance of Neuronal Microtubules and Controls Phosphorylation of Microtubule-Associated Proteins

Abstract: Microtubules (MTs) play an important role in elaboration and maintenance of axonal and dendritic processes. MT dynamics are modulated by MT-associated proteins (MAPs), whose activities are regulated by protein phosphorylation. We found that a member of the c-Jun NH(2)-terminal protein kinase (JNK) subgroup of MAP kinases, JNK1, is involved in regulation of MT dynamics in neuronal cells. Jnk1(-/-) mice exhibit disrupted anterior commissure tract formation and a progressive loss of MTs within axons and dendrites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
366
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(377 citation statements)
references
References 52 publications
10
366
0
Order By: Relevance
“…However, sustained and systemic JNK inhibition may cause various adverse side effects, because JNK also have other important functions in the development, differentiation, and insulin resistance (Figure 7b) (Waetzig and Herdegen, 2005). For example, JNK1 À/À mice showed severe impairment in the architecture of the brain, indicating that JNK phosphorylates microtubuleassociated proteins and contributes to normal brain functions (Chang et al, 2003;Bjorkblom et al, 2005). Therefore, Waetzig and Herdegen (2005) proposed the context-specific inhibition of JNK, that is, specific inhibition of damaging actions of JNK.…”
Section: Discussionmentioning
confidence: 99%
“…However, sustained and systemic JNK inhibition may cause various adverse side effects, because JNK also have other important functions in the development, differentiation, and insulin resistance (Figure 7b) (Waetzig and Herdegen, 2005). For example, JNK1 À/À mice showed severe impairment in the architecture of the brain, indicating that JNK phosphorylates microtubuleassociated proteins and contributes to normal brain functions (Chang et al, 2003;Bjorkblom et al, 2005). Therefore, Waetzig and Herdegen (2005) proposed the context-specific inhibition of JNK, that is, specific inhibition of damaging actions of JNK.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study went a step further and showed that retrograde transport of JNK signalling component after nerve injury contributes to the activation of c-Jun at the nucleus (Lindwall & Kanje 2005). Interestingly, in addition to regulating c-Jun, JNK proteins can directly regulate axonal microtubules by phosphorylating MAPs, including MAP-2 and MAP-1b (Chang et al 2003). JNK1 null mice show disrupted axon tracts of CNS neurons, such as the anterior commissure axons and spinal cord axons (Chang et al 2003).…”
Section: Axon Regenerationmentioning
confidence: 99%
“…[3][4][5][6] However, accumulating evidence supports a physiological role of JNK in regulating neurite formation and morphogenesis. [7][8][9][10][11][12] Pharmacological inhibition of JNK activity blocks axogenesis in hippocampal neurons, arguing for an essential role of JNK in neurite development. 13 Growth factors and signalling molecules, including secreted proteins of the Wnt family, have also been found to activate JNK for remodelling dendrites and axons, a process that relies on cytoskeletal rearrangement.…”
mentioning
confidence: 99%
“…Mice with Jnk1 À/À show abnormalities in neurite development, 7 whereas mice null for Jnk1 and Jnk2 show embryonic lethality due to severe neurological defects. 18 Jnk2 À/À mice, but not Jnk1 À/À mice, also show enhanced protection against brain damage in Parkinson's disease models.…”
mentioning
confidence: 99%